2015
DOI: 10.1007/s11046-015-9919-9
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation of Azole-Resistant Cryptococcus neoformans from Feline Cryptococcosis

Abstract: We report here, to the best of our knowledge, the first description of an in vitro fluconazole (FLZ)-resistant Cryptococcus neoformans var. grubii from a case of feline cryptococcosis. In vitro testing demonstrated that this isolate was resistant to FLZ (minimum inhibitory concentration, MIC, of 128 μg/ml) but remained susceptible to amphotericin B (0.064 µg/ml), itraconazole (0.38 µg/ml), voriconazole (0.023 µg/ml), and posaconazole (0.125 µg/ml). The predicted amino acid sequence of the lanosterol 14-α demet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The azoles are used extensively because they are significantly less expensive than other antifungal treatments and their overall antimycotic activity is relatively broad spectrum [6]. Azole drugs are used in: (1) treatment and prophylaxis of livestock (e.g., ringworm in cattle, aspergillosis in poultry, oomycete infections in aquaculture [7][8][9][10], (2) treatment in veterinary medicine (e.g., pets and zoo animals) [11,12], (3) crop protection (e.g., mildews and rusts of grains, fruits, vegetables), (4) plant protection (e.g., leaf spot on flowers, scrubs and trees, including the timber industry) [4], (5) protection of buildings (e.g., antifouling coatings) [13], (f) cosmetic and hygiene products [14], and (6) prophylaxis and treatment in medicine [15].…”
Section: Introductionmentioning
confidence: 99%
“…The azoles are used extensively because they are significantly less expensive than other antifungal treatments and their overall antimycotic activity is relatively broad spectrum [6]. Azole drugs are used in: (1) treatment and prophylaxis of livestock (e.g., ringworm in cattle, aspergillosis in poultry, oomycete infections in aquaculture [7][8][9][10], (2) treatment in veterinary medicine (e.g., pets and zoo animals) [11,12], (3) crop protection (e.g., mildews and rusts of grains, fruits, vegetables), (4) plant protection (e.g., leaf spot on flowers, scrubs and trees, including the timber industry) [4], (5) protection of buildings (e.g., antifouling coatings) [13], (f) cosmetic and hygiene products [14], and (6) prophylaxis and treatment in medicine [15].…”
Section: Introductionmentioning
confidence: 99%
“…5,24,32 Fluconazole is usually indicated for localised disease, 5 but some cryptococcal isolates have shown resistance with this drug. [33][34][35] Ketoconazole is a good choice for localised disease; however, it has more adverse effects than itraconazole. 4 Anorexia and weight loss have been reported in cats treated with ketoconazole after inoculation with C neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcosis is a common cause of systemic mycoses in cats and of zoonotic fungal infections 1,2) . Feline cryptococcosis in Japan is typically attributed to Cryptococcus neoformans (former name; Cryptococcus grubii) [3][4][5][6] . Feline cryptococcosis is generally treated with azoles, such as fluconazole (FLCZ) and itraconazole (ITCZ), which are effective against human and animal cryptococcoses and have few side effects 1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…FLCZ resistance, however, has been reported in isolates from human cryptococcoses [7][8][9] . Moreover, we have also described the first case of feline cryptococcosis in which an FLCZ-resistant C. neoformans strain was isolated from a cat 6) . Subsequent work demonstrated that multi-azole-resistant strains can readily be isolated from FLCZ-resistant strains by culturing in medium containing voriconazole (VRCZ) 10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation